WD40‐REPEAT 5a represses root meristem growth by suppressing auxin synthesis through changes of nitric oxide accumulation in Arabidopsis. (6th February 2018) - Liu, Wen‐Cheng; Zheng, Si‐Qiu; Yu, Zhen‐Dong; Gao, Xiang; Shen, Ran; Lu, Ying‐Tang
Summary: Although nitric oxide (NO) is known to regulate root growth, the factor(s) modulating NO during this process have not yet been elucidated. Here, we identified Arabidopsis WD40‐REPEAT 5a (WDR5a) as a novel factor that functions in root growth by modulating NO accumulation. The wdr5a‐1 mutant accumulated less NO and produced longer roots than the wild type, whereas the WDR5a overexpression lines had the opposite phenotype. The role of NO was further supported by our observation that the NO donor sodium nitroprusside (SNP) and the NO scavenger 2‐(4‐carboxyphenyl)‐4, 4, 5, 5‐tetramethylimidazoline‐1‐oxyl‐3‐oxide (cPTIO) rescued the root meristem growth phenotypes of the wdr5a‐1 and WDR5a overexpression lines, respectively. The regulation of root growth by WDR5a was found to involve auxin because the auxin levels were similar in SNP‐treated wdr5a‐1 and wild‐type roots, but higher in untreated wdr5a‐1 roots than in wild‐type roots. In addition, the wdr5a‐1 mutant had higher production and activity levels of the auxin biosynthetic enzyme TRYPTOPHAN AMINOTRANSFERASE OF ARABIDOPSIS1 (TAA1), in contrast to its reduced expression and activity in the WDR5a overexpression lines, and the increased root meristem growth in wdr5a‐1 was suppressed by treatment with l ‐kynurenine, which inhibits TAA1, as well as by mutating TAA1 . WDR5a therefore functions in root meristem growth by maintaining NO homeostasis, and thus TAA1‐mediated auxin biosynthesis. Significance Statement: Nitric oxide (NO) is known to regulate root growth, but the factor(s) modulating NO during this process have not yet been elucidated. In this study, we identified Arabidopsis WD40‐REPEAT 5a as a novel factor that functions in root meristem growth by modulating NO accumulation, and thus TRYPTOPHAN AMINOTRANSFERASE OF ARABIDOPSIS1 (TAA1)‐mediated auxin biosynthesis.